SPACE EXPLORATION: THE NEW FRONTIER - Patelis, Antonis; Tsalas , Giorgos; Tsogas, Ilias; Moutevelis , Nikiforos (Open Schools Journal for Open Science, 2025)
Space exploration involves the scientific investigation of the universe beyond Earth's atmosphere through a combination of astronomy, space technologies, and physical missions. Initially driven by astronomical observations, it has now evolved into a multidisciplinary domain encompassing uncrewed robotic probes and human spaceflights. With increasing involvement from private companies and groundbreaking innovations, space exploration holds immense promise for scientific discovery and the advancement of humanity. This presentation delves into its history, current missions, technological advancements, ethical and environmental challenges, and the prospects for future generations.